2013
DOI: 10.1038/ncomms3566
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt phosphate-modified barium-doped tantalum nitride nanorod photoanode with 1.5% solar energy conversion efficiency

Abstract: Spurred by the decreased availability of fossil fuels and global warming, the idea of converting solar energy into clean fuels has been widely recognized. Hydrogen produced by photoelectrochemical water splitting using sunlight could provide a carbon dioxide lean fuel as an alternative to fossil fuels. A major challenge in photoelectrochemical water splitting is to develop an efficient photoanode that can stably oxidize water into oxygen. Here we report an efficient and stable photoanode that couples an active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
309
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(327 citation statements)
references
References 41 publications
12
309
2
3
Order By: Relevance
“…Indeed, changes in the structural, electronic, optical, and morphological properties of the Ta 3 N 5 have been observed to have beneficial effects for improving its photocatalytic activity. [15][16][17][18][19][20][21][22][23] Among these studies, our recent work reported that not only the bulk properties but also the surface properties greatly affected the photocatalytic activity of Ta 3 N 5 . 24 A thin TaN layer on the surface (~ 2 nm), which formed depending on the synthesis method, was observed to change the energetic profile on the Ta 3 N 5 -electrolyte interface, thus changing the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, changes in the structural, electronic, optical, and morphological properties of the Ta 3 N 5 have been observed to have beneficial effects for improving its photocatalytic activity. [15][16][17][18][19][20][21][22][23] Among these studies, our recent work reported that not only the bulk properties but also the surface properties greatly affected the photocatalytic activity of Ta 3 N 5 . 24 A thin TaN layer on the surface (~ 2 nm), which formed depending on the synthesis method, was observed to change the energetic profile on the Ta 3 N 5 -electrolyte interface, thus changing the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considerable efforts have been made to improve the OER by introducing an active electrocatalyst. 23,25,[29][30][31][32] Cobalt oxide (CoO x ) has been extensively investigated as a cocatalyst, particularly for electrochemical and photoelectrochemical OER. 25,[29][30][31][32]34,35 Although many studies have reported improvement of the electrochemical OER using CoO x , studies on powder suspension systems are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the electronic and atomic structures of Fe 2 TiO 5 match well with TiO 2 and this would allow a good separation of the photogenerated hole carriers on the hybridized interface. In our design, the Fe 2 TiO 5 layer is sandwiched between TiO 2 and Co ox layers (Co ox layer is coated as the surface catalyst 19,20 21 . This closely contacting Fe 2 TiO 5 composite nanotube array guarantees a substantial visible light absorption and introduces hole-electron separation interfaces required for fast separation and effective transportation of the electron-hole pairs.…”
mentioning
confidence: 99%
“…5 Since that time, substantial efforts have been made to improve this photoelectrochemical water splitting activity by employing many different n-type semiconductor materials, such as TiO 2 [18][19][20] To enhance the efficiency of these materials, metal oxide modification of the semiconductor surfaces is often used, to generate oxygen evolution reaction (OER) cocatalysts that activate water oxidation to molecular oxygen. 9,15,[21][22][23][24][25][26][27] Among these, cobalt-phosphate (Co-P i ) and cobalt-borate (Co-B i ) cocatalysts electrodeposited from a dilute Co 2+ solution containing phosphate and borate electrolytes, respectively, are known to generate highly active OER cocatalysts. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] As an example, Nocera et al reported that a Si photoelectrode modified with a Co-P i cocatalyst exhibited high activity, with a solar energy conversion efficiency of 4.7%.…”
Section: Introductionmentioning
confidence: 99%